IL12-mediated liver inflammation reduces the formation of AAV transcriptionally active forms but has no effect over preexisting AAV transgene expression. - Irene Gil-Fariña; Marianna Di Scala; Lucia Vanrell; Cristina Olagüe; Africa Vales; Katherine A High; Jesus Prieto; Federico Mingozzi; Gloria Gonzalez-Aseguinolaza (PLoS ONE, 2013)
Recombinant adenoassociated viral vectors (rAAV) have proven to be excellent candidates for gene therapy clinical applications. Recent results showed that cellular immunity to AAV represents a major challenge facing the clinical use of systemic administration of these vectors. Interestingly, no preclinical animal model has previously fully reproduced the clinical findings. The aim of the present work was to enhance the T cell immune response against AAV capsid in mice by the administration of a rAAV expressing the immunostimulatory cytokine IL-12. Our results indicate that although IL-12 expression enhanced the AAV capsid-specific immune response it failed to eliminate transduced hepatocytes and long-term expression was achieved. We found that AAV-mediated transgene expression is altered by IL-12-induced liver inflammation. However, IL-12 expression has no effect over preexisting AAV-mediated transgene expression. IL-12 down-regulates AAV mediated transgene expression via induction of IFN-γ production by NK and T cells, but without altering the transduction efficiency measured by viral genomes. Our results indicate that liver inflammation affects the formation of transcriptionally active AAV vector genomes through an unknown mechanism that can be avoided by the use of DNA-demethylating or anti-inflammatory agents.